2017
DOI: 10.1186/s13000-017-0650-3
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling in uveal melanoma: technical reliability and correlation of molecular class with pathologic characteristics

Abstract: BackgroundA 15-gene expression profile test has been clinically validated and is widely utilized in newly diagnosed uveal melanoma (UM) patients to assess metastatic potential of the tumor. As most patients are treated with eye-sparing radiotherapy, there is limited tumor tissue available for testing, and technical reliability and success of prognostic testing are critical. This study assessed the analytical performance of the 15-gene expression test for UM and the correlation of molecular class with pathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…A prognostic 15-gene expression profile (15-GEP) test that predicts 5-year metastatic risk with Class 1A, 1B, and 2 results indicating low-, intermediate-, and highrisk groups, respectively, has been in clinical use for several years [14,15]. The test's accuracy has been documented in several retrospective and prospective studies involving more than 1,600 patients [14][15][16][17][18][19][20]; and its high technical reliability has also been reported [14,15,17,21]. It has been demonstrated that physicians use the test results in a risk-specific manner to guide metastatic surveillance recommendations including imaging, specialist referrals, laboratory testing, and clinical trial participation for adjuvant therapy [19,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…A prognostic 15-gene expression profile (15-GEP) test that predicts 5-year metastatic risk with Class 1A, 1B, and 2 results indicating low-, intermediate-, and highrisk groups, respectively, has been in clinical use for several years [14,15]. The test's accuracy has been documented in several retrospective and prospective studies involving more than 1,600 patients [14][15][16][17][18][19][20]; and its high technical reliability has also been reported [14,15,17,21]. It has been demonstrated that physicians use the test results in a risk-specific manner to guide metastatic surveillance recommendations including imaging, specialist referrals, laboratory testing, and clinical trial participation for adjuvant therapy [19,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Class 1 was therefore divided into class 1a and class 1b, where 1b predicts an intermediate risk of metastatic disease (Plasseraud et al. ). Increased expression of the gene PRAME , identified by a high level of PRAME mRNA, is predictive of metastatic disease among class 1 patients.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the above‐mentioned DNA‐based methods, gene expression profiling (GEP) uses the expression level of multiple genes to identify the profile of the tumour (Plasseraud et al. ). While all DNA‐based methods are limited by their risk of sampling error due to intratumoral heterogeneity, it is proposed that gene expression profiling is less affected by genetic heterogeneity (Onken et al.…”
Section: Introductionmentioning
confidence: 99%
“…Uveal melanoma (UM) is a rare but deadly intraocular cancer, with up to 50% of patients ultimately developing distant metastatic disease [1]. A 15-gene expression profiling (GEP) test commercially available as DecisionDx-UM (Castle Biosciences, Inc) is routinely used for prognostication of metastatic risk in UM patients and is considered standard of care in many ocular oncology centers across North America [2][3][4]. Testing is typically performed on fine needle aspirate biopsy (FNAB) taken from the primary tumor at the time of surgery for radiotherapy, or on formalin fixed paraffin embedded (FFPE) tissue taken from the primary tumor at the time of enucleation (eye removal).…”
Section: Introductionmentioning
confidence: 99%